Genetic and Morphometric Variability of Triatoma sordida (Hemiptera: Reduviidae) from the Eastern and Western Regions of Paraguay - Gonzalez-Britez, Nilsa E.; Carrasco, Hernán J.; Martínez Purroy, Clara Elena; Feliciangeli, M. Dora; Maldonado, Marisel; López, Elsa; Segovia, Maikell J.; Rojas de Arias, Antonieta (Frontiers in Public Health, 2014)
Triatoma sordida is widely distributed throughout the Chaco and the Eastern Region of Paraguay. It is associated to palm trees and artificial ecotopes located in peridomestic environments. The aim of this work was to determine genetic and morphometric variability and feeding behavior among population of T. sordida captured in domicile and peridomicile areas of Paraguay. Feeding contents and levels of genetic and morphometric variation were determined in 124 T. sordida from domicile and peridomicile populations of San Pedro and Paraguarí departments of the Eastern Region and Boquerón and Presidente Hayes departments of the Western region using Double Diffusion Gel, Random Amplified Polymorphic DNA and head and wings morphometry. Morphometric analysis revealed isolation of populations by geographic region and larger size in triatomine populations from the Western Region. RAPD showed no specific patterns for domicile and peridomicile populations. The estimator of diversity (FST; 0.08) and high gene flow obtained (Nm; 5.7) did not allow the establishment of genetic differentiation within the same region. The blood meal source showed that poultry feeding was 38% of host preferences and human blood was the second feeding preference (24%) in the insects from the Eastern Region while poultry feeding was predominant in those from the Western Region (30%). This work showed homogeneity between T. sordida populations of the same region and between domicile and peridomicile. The genetic structure was determined among T. sordida populations of both geographical regions suggesting differentiation associated to eco-geographical isolation by distance. It is important to notice that pattern feedings were different between the two regions. Further studies should be focused on how phenetic and genetic variations could be related to the adaptation capacity of these triatomine populations to domicile, increasing their vector potentiality in the transmission of Chagas disease.